v.2 - "Swamy,N. Maheshwara" (Hyderabad, 2003)
This book provides an detailed, comprehensive, contemporary and useful information on the law, judgments and executive policies relating to environmental protection in India. It also contains the text of all the Acts, Rules and Regulations related to environment protection, air pollution, water pollution, and other forms of pollution.
Keywords: Environmental law and legislation